Negotiating identity, originality, and agency in AI-assisted dissertation proposal writing among English education students - Widhiyanto, Widhiyanto; Haryanti, Rahayu Puji; Mutiaraningrum, Ira; Anggraeni, Candradewi Wahyu; Suryani, Lilis; Yafi, Mohammad Ali (Universitas Mulawarman, 2025)
This study examined the diverse approaches doctoral students take to developing an academic voice when utilizing AI. It examines the manifestation of academic integrity and agency, as well as the interplay among these constructs, through a case study. Thematic analysis, as a data analysis tool, from the responses of six doctoral students enrolled in the Proposal Dissertation Course, sheds light on the critical acceptance of AI. The results of the focus-group discussion and students’ reflective journals reveal that AI is recognized as applicable but does not replace human critical thinking in the manual investigation process. Research shows that students build academic identity through strategies such as making AI a discussion partner to maintain the author’s voice. They also maintain academic integrity by verifying AI sources, avoiding unreal citations, and manually paraphrasing the text. Students leverage AI for technical tasks and time management yet remain non-reliant and edit AI output to ensure it remains original work.